Sternal Cleft With Coarctation of Aorta and Vascular Anomalies - Learning Point in Young Stroke - Jiun, Koa Ai; Sim, Teh Yong; Ruwei, Lim (Malaysian Journal of Medicine and Health Sciences, 2022)
Sternal cleft is a rare congenital anomaly that is known to be associated with other congenital abnormalities in particular coarctation of aorta and vascular anomalies. We present a case of a young teacher who presented with recurrent episodes of ischemic stroke. During the workup to look for the cause of stroke, it was discovered that this patient had complete midline sternal cleft with underlying coarctation of aorta and left subclavian artery aneurysm. We wish to highlight the relation between the presence of sternal cleft and coarctation of aorta as well as vascular anomalies as one of the rare cause of young stroke.